Caregiver-guided pain coping skills training for patients with advanced cancer: Background, design, and challenges for the CaringPals study. (June 2019) - Porter, Laura S; Samsa, Gregory; Steel, Jennifer L; Hanson, Laura C; LeBlanc, Thomas W; Bull, Janet; Fischer, Stacy; Keefe, Francis J
Background/Aims: Pain is a major concern of patients with advanced cancer and their caregivers. There is strong evidence that pain coping skills training interventions based on cognitive-behavioral principles can reduce pain severity and pain interference. However, few such interventions have been tested for patients with advanced cancer and their family caregivers. This study aims to test the efficacy of a caregiver-guided pain coping skills training protocol on patient and caregiver outcomes. Methods: A total of 214 patients age ≥18 with Stage III–Stage IV cancer and moderate to severe pain, along with their family caregivers, are being identified and randomized with a 1:1 allocation to the caregiver-guided pain coping skills training intervention or enhanced treatment-as-usual. Dyads in both conditions receive educational resources on pain management, and the caregiver-guided pain coping skills training intervention includes three weekly 60-min sessions conducted with the patient–caregiver dyad via videoconference. Measures of caregiver outcomes (self-efficacy for helping the patient manage pain, caregiver strain, caregiving satisfaction, psychological distress) and patient outcomes (self-efficacy for pain management, pain intensity and interference, psychological distress) are collected at baseline and post-intervention. Caregiver outcomes are also collected 3 and 6 months following the patient's death. The study is enrolling patients from four tertiary care academic medical centers and one free-standing hospice and palliative care organization. The primary outcome is caregiver self-efficacy for helping the patient manage pain. Results: This article describes challenges in the design and implementation of the CaringPals trial. Key issues for trial design include the identification and recruitment of patients with advanced cancer and pain, and the follow-up and collection of data from caregivers following the patient's death. Conclusion: The CaringPals trial addresses a gap in research in pain coping skills training interventions by addressing the unique needs of patients with advanced cancer and their caregivers. Findings from this study may lead to advances in the clinical care of patients with advanced cancer and pain, as well as a better understanding of the effects of training family caregivers to help patients cope with pain.